Cemento-ossifying fibroma in the anterior region of the mandible: a case report emphasizing a conservative surgical management - Cotter, Helena Miguel; Elias, Rogério de Andrade; Ribeiro, Ana Carolina Prado; Vargas, Pablo Agustin; Lopes, Marcio Ajudarte; Santos-Silva, Alan Roger; Rocha, André Caroli (Journal of Oral Diagnosis, 2025)
Cemento-ossifying fibroma (COF) is a slow-growing, well-defined unilocular benign mesenchymal odontogenic tumor, that can have sclerotic edges and mixed areas. This case report details a conservative surgical treatment approach for COF that preserved both the cortical basal bone and the tooth segment. A thirty-three-year-old female presented with an asymptomatic extensive lesion in the anterior mandible, manifesting mild facial asymmetry, with one year of evolution. Imaging revealed a mixed dense lesion with sclerotic edges, with extension to the periapex of the teeth 33-44, expanding and thinning the cortical bone. Histopathology confirmed COF, showing fibrous stroma with spherical cementoid calcifications, overlayed with intact bone tissue. Conservative surgery was performed combining enucleation and curettage, with peripheral ostectomy, maintaining the cortical basal bone from the mandibulae, and tooth by apicoectomies. Three- and ten-months postoperative imaging displayed peripheral bone neoformation at the site, indicating effectiveness in the short-term follow-up, with no evidence of residual disease or recurrence.